Amino acids critical for the functions of the bovine papillomavirus type 1 E2 transactivator. - Brokaw, J L (1996)
The N-terminal domain of the bovine papillomavirus type 1 E2 protein is important for viral DNA replication, for transcriptional transactivation, and for interaction with the E1 protein. To determine which residues of this 200-amino-acid domain are important for these activities, single conservative amino acid substitutions have been generated in 17 residues that are invariant among all papillomavirus E2 proteins. The resulting mutated E2 proteins were tested for the ability to support viral DNA replication, activate transcription, and cooperatively bind to the origin of replication with the E1 protein. We identified five mutated proteins that were completely defective for transcriptional activation and either were defective or could support viral DNA replication at only low levels. However, several of these proteins could still interact efficiently with the E1 protein. In addition, we identified several mutated proteins that were unable to efficiently cooperatively bind to the origin with the E1 protein. Although a number of the mutated proteins demonstrated wild-type activity in all of the functions tested, only 3 out of 17 mutated viral genomes were able to induce foci in a C127 focus formation assay when the mutations were generated in the background of the entire bovine papillomavirus type 1 genome. This finding suggests that the E2 protein may have additional activities that are important for the viral life cycle.